Epidemiological determinants and characteristics of road Traffic Accident cases admitted to KGMU, a Tertiary Care Hospital - Misra, Rajeev; Tiwari, Sandeep; Sharma, Amar Chandra; Nigam , Chakori; Bharti, Surendra (Indian Journal of Community Health, 2025)
Background: Road traffic accidents (RTAs) represent a major public health concern, particularly in low- and middle-income countries like India, where they contribute substantially to both morbidity and mortality. Aim and Objective: To evaluate the epidemiological determinants, patterns of injury, and outcomes of healthcare related road traffic accidents in order to determine risk factors and recommend evidence-based prevention and management strategies. Methodology: A prospective observational hospital-based stdy was performed. Patients admitted due to road traffic accidents between 2019–2020 were enrolled. Data were collected within 24–48 hours of admission using a structured, pre-tested questionnaire covering socio-demographic details, vehicle type, safety measures, and injury characteristics. In cases where patients could not respond, attendants or relatives were interviewed. Data were entered into Microsoft Excel 2013 and analyzed using SPSS version 26. Results: Among 821 Road traffic accidents patients, 91% were males, with two-wheelers involved in 72.6% of cases. Only 6.3% used helmets/seatbelts. Mixed injuries (64.8%) predominated, and most patients were drivers (72.5%), often referred from district hospitals (43.4%). Conclusion: Road traffic accidents largely affect young male two-wheeler drivers with poor safety compliance. Strengthening law enforcement, road safety awareness, and trauma care at peripheral centers is crucial to reduce morbidity and mortality.